2022
DOI: 10.2147/jir.s364945
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of the Extract from the Fungus Coriolus versicolor on Lipopolysaccharide-Induced Cytokine Production in RAW 264.7 Macrophages Depending on the Lipopolysaccharide Concentration

Abstract: Extract from the fungus Coriolus versicolor (CV) is classified as an immunological response modifier. Previously, we have shown that this extract induces interleukin 6 (IL-6)-related extension of lipopolysaccharide (LPS)-induced fever. This study investigated the effect of CV extract on the production of pro-inflammatory cytokines and the expression of components of signal transduction pathways leading to the secretion of cytokines from RAW 264.7 macrophages stimulated with different doses of LPS. Methods: RAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In our previous studies, we observed many times that macrophages are key cells involved in response to LPS [21,35]. It is commonly accepted that they may exhibit anti-cancer or pro-cancer properties, depending on their M1 and M2 phenotypes that are associated with the production of different cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we observed many times that macrophages are key cells involved in response to LPS [21,35]. It is commonly accepted that they may exhibit anti-cancer or pro-cancer properties, depending on their M1 and M2 phenotypes that are associated with the production of different cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…An indicator of endotoxin tolerance (ET) is the decreased production of pro-inflammatory cytokines such as TNFα and IL-6 from macrophages during continued endotoxin exposure. Therefore, to determine the induction of ET, in this study, we evaluated the level of protein expression of TNFα and IL-6 in macrophages treated with a dose of 100 ng/mL of LPS based on the previous literature and preliminary data produced in our laboratory [21].…”
Section: Endotoxin-tolerant Macrophages Displayed Decreased Expressio...mentioning
confidence: 99%
“…Additionally, during treatment of cells with lower concentrations of lipopolysaccharide, the extract increased cytokine production, while higher dose of lipopolysaccharide led to their reduced synthesis. In other words, C. versicolor extract showed an antagonistic or additive effect according to lipopolysaccharide concentration [ 52 ].…”
Section: Mechanism Of Cell Proliferation and Immunomodulation Propertiesmentioning
confidence: 99%
“…RAW264.7 and J774A.1 cells were seeded in 24-well plates at the density of 5 × 10 5 cells/well. Following overnight pre-incubation and a 1 h pretreatment with TAK-242 at a concentration of 0.1 µM at 37 • C [44], 100 ng/mL of LPS was added, and cells were incubated for 2 h or 24 h (depending on the experiment) at 37 • C or 39 • C. After incubation, the cells were rinsed with ice-cold PBS and lysed in 100 µL of a 1 x RIPA buffer supplemented with 1% SDS and 0.5% protease inhibitor cocktail (all reagents were purchased from Sigma Aldrich). Following mechanical homogenization, the lysates underwent centrifugation to eliminate cellular debris.…”
Section: Western Blot Analysismentioning
confidence: 99%